THE HIDDEN TREASURE OF THE FOREST: THE RISE OF NON-TIMBER FOREST PRODUCTS (NTFPS) AND CIRCULAR ECONOMY OPPORTUNITIES BASED ON NATURAL COMMODITIES - Mahmud, Khalid; Idris, Adam; Ismail, Nadiah (Journal of Selvicoltura Asean, 2026)
The global push toward a Circular Economy (CE) demands leveraging regenerative resources, making Non-Timber Forest Products (NTFPs) critical assets for a sustainable bio-economy. This study addresses the profound structural inefficiency within current NTFP value chains, which operate on a linear model, resulting in significant material waste and limiting local economic value. The core research objective was to rigorously assess material efficiency and identify the governance barriers preventing the transition to zero-waste systems, thereby developing a prescriptive NTFP-Circular Economy (NTFP-CE) Model. The methodology employed a comparative process mapping design, integrating Mass Balance Analysis across twelve diverse processing units with qualitative interviews focused on institutional failure and technology adoption. Findings demonstrate a critically low average Conversion Efficiency Rate (CER) of 61%, revealing that 39% of raw forest biomass is discarded as unused residue. This inefficiency is not primarily technological, but fundamentally institutional, driven by the absence of formal Residue Governance Standards and Intellectual Property Rights (IPR) protection. These institutional failures collectively block the necessary industrial investment in zero-waste bio-refinery systems. The study concludes that the NTFP-CE Model provides the essential, evidence-based framework for policy intervention, arguing that standardized residue management and policy-driven risk-sharing are vital to transform discarded residues into high-value industrial feedstocks, ensuring sustainable and equitable forest bio-economy development.